THE EFFECT OF BRAND TRUST AND PERCEIVED RISK ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION (A STUDY OF DAVIENA SKINCARE CUSTOMERS ON TIKTOK SHOP) - Andhika Ayu Luthfiyani; Muhammad Yani; Mochamad Rizal Yulianto; Rita Ambarwati Sukmono (International Journal of Artificial Intelligence for Digital Marketing, 2025)
Objective: The purpose of this study is to analyze the effect of brand trust and perceived risk on customer loyalty, customer satisfaction as a mediator, for Daviena Skincare products distributed by TikTok Shop. The issue of product overclaims present in the marketing of skincare products, specifically for Indonesia generally and for Daviena Skincare in particular, contributed to consumer uncertainty, which can hamper brand trust, perceived risk, and customer loyalty. Method: The approach and strategy for this study are quantitative, specifically represented by surveys, with 150 respondents who are customers of Daviena Skincare, having transacted at least twice at TikTok Shop. Results: The findings from this study show that brand trust and perceived risk affected customer satisfaction on TikTok Shop, customer satisfaction affected customer loyalty, and brand trust and perceived risk directly affected customer loyalty. The findings show that customer satisfaction can mediate the relationship between Brand Trust, Perceived Risk, and Customer Loyalty for Daviena Skincare on TikTok Shop. Novelty: The development of social media and e-commerce, specifically TikTok Shop, has fueled competition in the local skincare industry in Indonesia, highlighting the role of customer satisfaction as a mediating variable in the relationship between brand trust, perceived risk, and customer loyalty for Daviena Skincare products distributed through TikTok Shop.